2018
DOI: 10.12753/2066-026x-18-089
|View full text |Cite
|
Sign up to set email alerts
|

Virtualized Video Conferencing for Elearning

Abstract: Video conferencing has been commercially available since the video technology has become accessible on a variety of equipment, from room-based to handheld devices. The technology has also reached the point where it is viewed as a necessity and not just a nicety. The ubiquity and accessibility of video conferencing technology can save time and money across the spectrum of business processes, especially when comes to call centers. We propose a solution that can develop the communication with callers and provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Elsden et al (2022) found that the ubiquity of video conferencing facilitates not only remote work and learning but also enables social and personal interactions. Suciu et al (2018) noted that the ubiquity and accessibility of video conferencing can save time and money across various business processes, due to which VC apps are now viewed as a necessity, not just a nicety. The studies are a few examples depicting ubiquity as a most important characteristic of VC apps.…”
Section: Conceptual Research Model and Hypothesesmentioning
confidence: 99%
“…Elsden et al (2022) found that the ubiquity of video conferencing facilitates not only remote work and learning but also enables social and personal interactions. Suciu et al (2018) noted that the ubiquity and accessibility of video conferencing can save time and money across various business processes, due to which VC apps are now viewed as a necessity, not just a nicety. The studies are a few examples depicting ubiquity as a most important characteristic of VC apps.…”
Section: Conceptual Research Model and Hypothesesmentioning
confidence: 99%
“…Video conferencing systems have been in use for a number of years [55], but it is only in the last two years that they have become part of everyday life for many people. From the start of the first lockdown, video conferencing systems have allowed us to carry out numerous activities from home, such as distance learning in schools and universities, office and many other types of work, and social interaction [33], [44], and [59] that otherwise would not have been possible due to restrictions on face to face activities. These tools have evolved over the last two years, including the development of additional features and interface functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…WebRTC is a realtime communication technology that has integrated standards of API (Application Programming Interface) with real-time multimedia transfer such as voice and video (including codes) available to a web browser without traditional plug-in components using JavaScript code. [1] [3] Recently, there was an increase in the new platform implementation of real-time communications services: browser embedded application or "web application." Among these applications, WebRTC has received significant interest since a lot of new versions of inherently supports this API common browsers, namely Google Chrome and Mozilla Firefox.…”
Section: Introductionmentioning
confidence: 99%